Self-efficacy of caregivers in helping cancer patients to deal with pain - Nor, Nur Atiqah Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Self-efficacy is the person's learned to success. Expectations of person to success will lead to the rise of confident level and increased the self-efficacy to perform the desire behavior. The objective of the study is to determine the level of self-efficacy of caregivers and its relationship with gender and stages of cancer. This study is a cross-sectional study using the Self-Efficacy Scale questionnaire. Sixty five respondents were participated and data were analyzed by using Independent t Test and One-Way ANOVA The level of self-efficacy of the caregivers had shown low, moderate, high and very high level of self-efficacy. By using Independent t Test, it shows that there are no significant difference of gender and self-efficacy of the caregivers; on the other hand by using One-Way ANOVA, it shows that there is significant difference of the self-efficacy and stages of cancer. The higher the stages of cancer, the lower level of self-efficacy. As the conclusion self-efficacy does not associated by gender of the caregivers but it depends on person expectations to success where as long as the caregivers believe they can do it, then they will able to perform it. The progressions of the disease bring out more stressor to the caregivers and their self-efficacy also was affected. Therefore, the effective communication between the health care provider and the family caregivers should be emphasized. Taken as a whole, the health care provider especially nurses need to play their role and educate family caregivers regarding the progression of disease.